Peradaban Islam di Asia Tenggara - Tri Wantini; Nabila Aulia Ramadhani; Cinta Zahra Dwi Putri Br. Purba; Athalia Dimansyah; Ajeng Dwi Kartika; Ria Suherman; Sirojul Fuadi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Southeast Asia has long held a strategic position in global maritime trade since the pre-Islamic era. Through interactions with Arab, Persian, and Indian merchants, Islam was introduced to the region not through military conquest, but via peaceful and cultural means, particularly through trade and Sufi missionary activities. The Islamization process unfolded gradually, beginning in major port cities such as Samudera Pasai, Malacca, and Gresik, with significant support from local elites. This study employs a qualitative descriptive-analytical approach using library research methods, drawing from historical records, Malay Islamic manuscripts, and recent academic studies. The findings reveal that Islamic civilization in Southeast Asia manifested in the form of Islamic sultanates, traditional Islamic educational institutions (pesantren and pondok), and rich cultural expressions such as arts, literature, and architecture shaped by local aesthetics. This acculturation process gave rise to a moderate, inclusive, and adaptive form of Islam. In the modern era, Islam in this region continues to evolve in response to global challenges through institutional innovation and the contextualization of Islamic values. Therefore, Islam in Southeast Asia is not merely a religious system, but a civilizational force that shapes a distinctive and sustainable regional identity.